Implications of a third gender for elite sports - Harper, J.; Martinez-Patino, M.-J.; Pigozzi, F.; Pitsiladis, Y. (Current Sports Medicine Reports, 2018)
The highest court in Germany ruled recently in favor of the introduction of a third gender category for individuals who do not identify as either male or female or are born with an ambiguous sexual anatomy. This ruling is in line with at least 10 nations or states that allow a third legal gender. This perspective outlines the implications of a third gender for elite sport and is a summary of proceedings of a session entitled ``Beyond Fairness: The Biology of Inclusion for Transgender and Intersex Athletes`` at the 10th European Sport Medicine V Congress of the European Federation of Sports Medicine Associations (EFSMA). In conclusion, to uphold the Olympic Charter and ensure meaningful sporting competition, it is necessary to use an evolving evidence-based scientific method to separate athletes into male and female categories. Although imperfect, the best currently available scientific approach is the use of serum testosterone levels. It is helpful to view the separation of athletes into male and female categories as the determination of an athletic gender. If the idea of an athletic gender is adapted, the increased use of this concept will result in clearer sporting policies and a reduction in the discord between various factions in the very complex world of sex, gender, and sport.